Deflection Of Rigid Pavement Nailed Slab System With Lateral Loads - Adolf Situmorang (International Conference on Coastal and Delta Areas, 2017)
Indonesia is a country with a soft land area of about 60 million ha or about 30% of the total land area of about 198.6 million ha. Soft soils include peat soils, clay soils and other soft soils scattered throughout the province in Indonesia. If a rigid pavement or flexible pavement rigid pavement layer is built on soft soil without prior repair on the ground, it will be damaged as cracks in the concrete or wavy in the asphalt layer, this is due to soft soils, Which is not uniform which can cause damage to the pavement layer. Rigid pavement with nailed slab system is one solution to overcome the frequent breakdowns of soft soils, and it is hoped that using pavement models will increase the pavement strength when placed on soft soil. This pavement consists of 15 cm plates and 1-2 m long poles, 15-20cm in diameter, which are monolithically coupled with plates. From the results of several previous studies that pavement is more resistant seen from small plate deflection when compared with without using a pile or anchor. But due to repeated lateral load will cause a gap between the pile and the subgrade around the pile that can reduce the friction value along the pile so as to reduce the modulus of subgrade reactions. Keywords : modulus of subgrade reactions, lateral loads, soft soil